2018
DOI: 10.1007/s10278-018-0062-2
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Implementation of Deep Convolutional Neural Networks for MRI Segmentation

Abstract: Image segmentation is one of the most common steps in digital image processing, classifying a digital image into different segments. The main goal of this paper is to segment brain tumors in magnetic resonance images (MRI) using deep learning. Tumors having different shapes, sizes, brightness and textures can appear anywhere in the brain. These complexities are the reasons to choose a high-capacity Deep Convolutional Neural Network (DCNN) containing more than one layer. The proposed DCNN contains two parts: ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…In this study the DLM provided high segmentation performance, with the results being comparable to research focusing on automated glioblastoma and glioma segmentation 17,19,27,28 . In this context, Perkuhn et al reported DSCs between 0.62 and 0.86 for the differing tumor components of glioblastoma while using the same DLM as in the present study 17 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study the DLM provided high segmentation performance, with the results being comparable to research focusing on automated glioblastoma and glioma segmentation 17,19,27,28 . In this context, Perkuhn et al reported DSCs between 0.62 and 0.86 for the differing tumor components of glioblastoma while using the same DLM as in the present study 17 .…”
Section: Discussionsupporting
confidence: 82%
“…17 Using a different CNN, Menze et al and Hoseini et al calculated DSCs of 0.74-0.85 and 0.84-0.90, for glioma segmentations, respectively. 19,27 Kickingereder et al reported DSCs between 0.89 and 0.93 for an artificial neural network trained on a larger cohort of patients with glioblastoma. 28 Given the comparable results of the study by Perkuhn et al 17 and the present study, a DLM trained on gliomas and achieving accurate segmentation of glioblastomas can be applied on PCNSL, despite their often different appearance and overall complex tumor structure without noticeably decreasing segmentation performance.…”
Section: Discussionmentioning
confidence: 99%
“…We already used the DCNN model to improve segmentation of MR images. The model was evaluated on the public BRATS 2016 dataset with patch-based approach for segmentation, resulting in dice similarity metric 0.90 for complete, 0.85 for core, and 0.84 for enhancing regions [26].…”
Section: Previous Deep Learning Approaches To Brain Tumor Segmentationmentioning
confidence: 99%
“…In recent years, the approach of deep convolutional neural networks (CNN) of sequential type has dominated the field of image classification and becoming superior to the traditional approach of handcrafted features [12][13][14] . In contrast to hand-crafted features, deep CNNs could learn rich highly abstract image features from the training dataset of large scale images to represent complex objects in an efficient way and can be faster.…”
Section: Introductionmentioning
confidence: 99%